Integrated Reporting Research in Turkiye: A Systematic Literature Review (2012-2022) - Emine Serap Kurt (Muhasebe Enstitüsü Dergisi)
Financial reporting is a core aspect of the traditional reporting approach but falls short of responding to stakeholders’ requests for sustainability and non-financial information. One of the most crucial communication tools companies use to communicate how they create value to their stakeholders is integrated reporting, which was born out of this requirement and has become a crucial component of the growing corporate reporting ecosystem. Integrated reporting provides agility and helps with sustainability management and the non-financial risks businesses face that operate in an uncertain environment. Integrated reporting additionally improves an organization’s accountability and transparency, which makes raising capital easier. The foreign and Turkish literature continue to develop regarding the field of integrated reporting, which has grown in popularity and importance in recent years, particularly since the 2000s. The purpose of this study is to identify research gaps that could be the subject of future studies by analyzing the theses and articles on integrated reporting that have been written in Turkiye. The study uses the systematic literature review approach to assess the theses and articles concerning integrated reporting that were published in Türkiye between 2012-2022. The scan was conducted on November 20, 2022 using research words connected to integrated reporting in the TRDizin, DergiPark, and National Thesis Center websites and included only Turkish and English papers in peer-reviewed journals as well as graduate student theses. The final sample consists of 102 articles and 63 theses. The earliest article and thesis were found to have been written in 2012 and 2016, respectively. In 2021 and 2022, the scanned studies that examine this topic were seen to have increased. The publication of the revised integrated reporting framework in 2021 along with its simultaneous translation into Turkish was concluded to have had no noticeable impact. The existing studies were determined to include general information about integrated reporting, the impact of integrated reporting on company performance, and the compatibility of integrated reporting guidelines and content items. Future research can focus on value creation, integrated thinking, integrated reporting, and sustainability, as well as the quality of integrated reporting and its causes.